The influence of the charge-to-mass ratio of the charged water mist on a methane explosion. (May 2016) - Yu, Minggao; Wan, Shaojie; Xu, Yongliang; Zheng, Kai; Liang, Donglin
Abstract: To study the influence of the charge-to-mass ratio of a charged water mist on a methane explosion, the induction charging method was used to induce charge on a normal water mist; a mesh target method was employed to test the charge-to-mass ratio of its droplets. The propagation images, propagation average velocities, and overpressures of a methane explosion suppressed by charged water mist were analysed. The influence of the charge-to-mass ratio of the suppressant water mist on a methane explosion was studied. Results show that the explosion temperature, propagation average velocity, and peak overpressure deceased more obviously with charged water mist than ordinary water mist. With increasing charge-to-mass ratio, the suppression effect of the charged water mist underwent a significant increase. Under experimental conditions, compared with ordinary water mist, when the charge-to-mass ratio was 0.445 mC/kg and the mist flux was 4 L, the minimum flame propagation average velocity was 3.456 m/s, with a drop of 2.37 m/s (40.68%), and the peak overpressure of the methane explosion was 10.892 kPa, with a drop of 10.798 kPa (49.78%). The suppression effect is considered from the changes of the physico-chemical properties of the water mist as affected by the applied charge-to-mass ratio. Highlights: A normal water mist was charged by induction. Effects of water mists with different charge-to-mass ratios on explosion were studied. The characteristics of methane explosion suppressed by charged water mist were analysed. With increasing charge-to-mass ratio, the suppression effect of charged water mist underwent a significant increase. The suppression effect is considered from the changes of physico-chemical properties of water mist as affected by charging.